The Impact of The Government’s Rehabilitation Program on Children in Conflict with The Law in Iloilo City - Bacusa Jr., Doroteo; Cadangin, Lea Mae; Del Monte, Kimberly; Despi, Reme; Nerios, Isaac; Tenebro, Retchel; Mobo, Froilan D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research aims to analyze the effectiveness and outcomes of the government's rehabilitation program for children in conflict with the law in Iloilo City, Region 6. This study will utilize a quantitative ap-proach to gather information about the demographic profile and the impact of the government’s rehabilitation program on various stake-holders, including the social workers, barangay officials, house par-ents, guardians, and the CICL. These respondents were chosen to pro-vide a comprehensive perspective on the rehabilitation program and its challenges, aiming to identify areas for improvement and growth. In collaboration and partnership with the government and non-government organizations, this rehabilitation center aims to promote quality education through intervention, diversion, and rehabilitation programs and services that seek to address the best interest, welfare, and development of the children in conflict with the law and children at risks, shaping them into becoming a self-reliant, productive and God-fearing individual, upon reintegration with their families and in the communities.